10x + 17 = 4x - 16x = -18x = -3
18x + 5
Are you sure that the given expressions are right? Because we are dealing with complex numbers (a little bit work for this kind of exercise).ab = 4x + 8bc = 8x + 4ac = 18x - 11b = a/(4x + 8)c = b/(8x + 4) = [a/(4x + 8)[/(8x + 4) = a/[(4x + 8)(8x + 4)]c = a/(18x - 11)a/[(4x + 8)(8x + 4)] = a/(18x - 11) this happens only when:(4x + 8)(8x + 4) = (18x - 11)32x^2 + 16x + 64x + 32 = 18x - 1132x^2 + 62x + 43 = 0x = [-62 ± √(62^2 - (4)(32)(43)]/[(2)(32)]x = [-62 ± √(-1660)]/64x = [-62 ± i√(1660)]/64x = -62/64 ± i√(1660/4096) (64^2 = 4096)x = -31/32 ± i√[415/1024]Substitute -31/32 ± i√[415/1024] for x, and find the value of ab, bc, and ac.ab = 4x + 8bc = 8x + 4ac = 18x - 11
I would subtract [ 2x (4x + 9) ] .
2(4x - 3)(x + 3)
7Improved Answer:8x2-18x+9 = (4x-3)(2x-3)
10x + 17 = 4x - 16x = -18x = -3
18x + 5
(2x + 1)(4x + 7)
Are you sure that the given expressions are right? Because we are dealing with complex numbers (a little bit work for this kind of exercise).ab = 4x + 8bc = 8x + 4ac = 18x - 11b = a/(4x + 8)c = b/(8x + 4) = [a/(4x + 8)[/(8x + 4) = a/[(4x + 8)(8x + 4)]c = a/(18x - 11)a/[(4x + 8)(8x + 4)] = a/(18x - 11) this happens only when:(4x + 8)(8x + 4) = (18x - 11)32x^2 + 16x + 64x + 32 = 18x - 1132x^2 + 62x + 43 = 0x = [-62 ± √(62^2 - (4)(32)(43)]/[(2)(32)]x = [-62 ± √(-1660)]/64x = [-62 ± i√(1660)]/64x = -62/64 ± i√(1660/4096) (64^2 = 4096)x = -31/32 ± i√[415/1024]Substitute -31/32 ± i√[415/1024] for x, and find the value of ab, bc, and ac.ab = 4x + 8bc = 8x + 4ac = 18x - 11
I would subtract [ 2x (4x + 9) ] .
2(4x - 3)(x + 3)
When you check an answer by using it in another sum e.g2x+7=13x=3substitute to second-4x+6=18x=3 which is correct
y=4x-8y=2x+10Substitute (4x-8) for y in the second equation and solve for x:4x-8=2x+102x=18x=9Now solve for y:y=4(9)-8=28(9,28)
(2x4) + (8x3) + 18x 8 + 24 + 18x 32 + 18x
In dividing (18x⁹ -12x⁷ -8x⁶ -2x³) ÷ -2x² you could do long division, but as the divisor contains a single term like a normal fraction each term of the dividend can be divided by the divisor and summed together: (18x⁹ -12x⁷ -8x⁶ -2x³) ÷ -2x² = (18x⁹ -12x⁷ -8x⁶ -2x³)/(-2x²) = 18x⁹/(-2x²) + -12x⁷/(-2x²) + -8x⁶/(-2x²) + -2x³/(-2x²) = (18 ÷ -2)(x⁹ ÷ x²) + (-12 ÷ -2)(x⁷ ÷ x²) + (-8 ÷ -2)(x⁶ ÷ x²) + (-2 ÷ -2)(x³ ÷ x²) = -9x⁹⁻² + 6x⁷⁻² + 4x⁶⁻² + 1x³⁻² = -9x⁷ + 6x⁵ + 4x⁴ + x
18x= 19818x/18 = 198/18x = 11